Hubungan Teman Sebaya Dengan Perilaku Konsumsi Tablet Tambah Darah Pada Remaja Putri SMAN 14 Makassar - Putri; Harpiana Rahman; Rezky Aulia Yusuf (Window of Public Health Journal, 2025)
Anemia is a significant Public Health problem worldwide. Anemia in adolescent girls can be caused by various factors, one of which is a lack of consumption of foods high in iron. This study, which used a quantitative method and a cross-sectional study design with a sample of 80 respondents, aimed to determine the relationship between peers and the habit of consuming iron tablets in adolescent girls at SMAN 14 Makassar. The data processing in this study was computerized, using SPSS Software to produce clear and correct information in accordance with the objectives of the study. The data analysis method used was Univariate and Bivariate with the Chi-square test. The study results showed a significant relationship between peers and the behavior of consuming iron tablets in adolescent girls at SMAN 14 Makassar, which has practical implications for public health interventions, with a p-value of 0.000 <0.05. The conclusion of the study is that peer variables have a relationship with the behavior of consuming iron tablets in adolescent girls at SMAN 14 Makassar in 2024. This study suggests that adolescents invite their peers to increase interest in positive things, such as routinely consuming iron tablets according to the recommendations that have been set, thereby empowering them to take control of their health.